FINANCING THE JUDICIARY AUTHORITIES IN RUSSIA, BELARUS AND KAZAKHSTAN - V. V. Litvinova (Финансы: теория и практика)
The purpose of the paper is to show the prospects and risks of the formation of uniform judiciary bodies in Russia, Belarus and Kazakhstan. To this end, the paper analyzes statutory instruments regulating the procedure of funding the judiciary bodies in the above countries, in particular Constitutions, codes, constitutional and federal laws. The problems of social guarantees to judges are identified; the system of financing the courts as well as funding procedures adopted in Russia, Belarus and Kazakhstan are described. The study contains two comparative tables that demonstrate the differences between the legal systems of the states and possible areas of improvement and harmonization of their legislations. The first table shows the key characteristics of the systems of funding the judiciary bodies in Russia, Belarus and Kazakhstan, while the second table contains social protection guarantees for judges in the countries. Finally, the author puts forward a proposal that the number of courts in the Russian Federation should be reduced arguing that the budget financing of the judicial systems should be implemented separately for each individual court. Such a financing system ensures the maximum efficiency and independence of the judiciary system.